Strategy for Strengthening Science Techno Park (Case Study: Solo, Sragen and South Sumatra Techno Park) - Fajrin Nurul Haq; Siti Widharetno Mursalim (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Currently, various kinds of research and technology results are produced in Indonesia, but the problem is how far the results of research and technology can be adopted by the industry. In fact, with the increase in research output and technology produced, it is not proportional to the increase in the number adopted by the industry. Therefore, it is necessary to strengthen the Science Techno Park as an integrated area in developing research and technology results. The research approach used is qualitative with the aim of being able to examine strategies in strengthening the Science Techno Park. From the results of the research, it is known that the concept of BLUD and collaboration can be a strategy that is applied in Solo, Sragen and South Sumatra Techno Park.